Method for synthesizing lactide by cracking polylactic acid waste
Through a catalytic system where amino alcohol and acid catalysts work together, the problem of low efficiency in polylactic acid recovery and depolymerization production of lactide is solved, and efficient and low-cost lactide recycling is achieved, and high-purity products are obtained.
Patent Information
- Application Number
- CN202411279151.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-13
AI Technical Summary
In the prior art, the method of depolymerizing and producing lactide after polylactic acid recovery is low efficiency, slow reaction, long time, and the lactide recovery rate is not high, and a large amount of solvent is required for post-treatment, which is expensive.
Using amino alcohol and acid catalyst to promote the chain breaking and cleavage reaction of polylactic acid, a new catalytic system was designed, with higher efficiency in chain breaking reactions, fewer types of crude product impurities, and no large amount of solvent is required for it. Post-treatment enables efficient synthesis of lactide.
High-speed alcoholylation and cleavage of polylactic acid is achieved, the recovery rate of lactide is improved, the amount of catalyst is reduced, the cost of equipment is reduced, and the high-purity refined lactide is obtained, which is in line with the policy of sustainable development.
Smart Images

Figure BDA0005041110360000101 
Figure BDA0005041110360000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of material chemistry, in particular to a method for synthesizing polymer-grade lactide from polylactic acid waste. Background Art
[0002] Polylactic acid is a bio-based degradable polymer. Since polylactic acid is synthesized from renewable resources (corn starch, etc.) and can be degraded in the natural environment, its various characteristics make polylactic acid a potential solution to the problem of plastic pollution. At present, polylactic acid is often produced through the ring-opening polymerization of the intermediate lactide, and lactide is prepared industrially by a two-step method. The starting raw material lactic acid is prepolymerized to form lactic acid polymers, and then the lactic acid polymers are cracked to synthesize lactide. This method has the disadvantages of being time-consuming, having many steps, and high energy consumption. At present, technicians from various countries are looking for new lactide synthesis routes. One of the less reported methods is to recycle polylactic acid waste and depolymerize it to resynthesize lactide, which can solve the cost problem of polylactic acid waste landfill treatment and reduce the product cost of lactide.
[0003] However, there are still many problems in the technology of polylactic acid recycling and synthesizing lactide. CN102746270B describes a method for producing lactide by depolymerization after polylactic acid recycling, but the depolymerization step of the method only relies on the coordination insertion of the catalyst for chain breaking reaction, which is inefficient, thus causing the method to react slowly, take a long time, and the lactide recovery rate is not high. CN115403554 B adds fatty alcohols in the depolymerization step, but the reaction temperature is much higher than the boiling point of the fatty alcohols used, so that the fatty alcohols cannot be fully mixed with the molten polylactic acid, and the efficiency of the reaction of only fatty alcohols with polylactic acid is still not high, and a large amount of solvents need to be used to remove the added small molecule fatty alcohols after recovering lactide, which is costly. The above problems are technical problems that need to be solved in this field. Summary of the invention
[0004] The purpose of the present invention is to provide a method for synthesizing lactide by cracking polylactic acid waste. The method is different from the method of the existing invention patent that polylactic acid is chain-broken under the action of a single catalyst and then cracked by another single catalyst to generate lactide. A new catalyst system is designed. The catalyst system can promote chain-broken and cracked reactions at the same time. The advantages of this catalyst system are that the chain-broken reaction is more efficient and does not produce ester groups that cannot be used to synthesize lactide; the crude product of the reaction has fewer types of impurities and does not require a large amount of solvent for post-treatment, so that lactide can be synthesized in large quantities and efficiently; the chain-broken reaction and the cracking reaction are carried out in the same container, reducing the equipment cost; the amino alcohol and the acid catalyst used can be repeatedly used.
[0005] To this end, the technical solution of the present invention is to utilize the synergistic effect of amino alcohol and acid catalyst to promote the transesterification reaction in the alcoholysis step, achieve high-speed alcoholysis of polylactic acid, and at the same time, under the action of the acid catalyst, rapidly crack lactic acid oligomers into lactide and recover them. Specifically, it includes the following steps:
[0006] 1) Alcoholysis of polylactic acid:
[0007] The polylactic acid waste is crushed and added to a reaction container, and amino alcohol and an acid catalyst are added to the reaction container, and the polylactic acid is stirred at 180-230° C. for 1-2 hours to perform alcoholysis of the polylactic acid to prepare a lactic acid oligomer.
[0008] 2) Cleavage of lactic acid oligomers:
[0009] Lactic acid oligomers undergo dehydration cyclization reaction under the conditions of 180-230°C and -0.1-0.095 MPa vacuum to generate crude lactide.
[0010] 3) Purification of crude lactide.
[0011] The crude lactide is washed with water and then purified by a melt sweating device to obtain purified lactide.
[0012] Wherein, the polylactic acid waste in step 1) is a homopolymer, copolymer or blend of left-handed polylactic acid, right-handed polylactic acid, racemic polylactic acid or optically inactive polylactic acid; the polylactic acid content in the polylactic acid waste is 10% to 100%, and the number average molecular weight is 10 3 ~10 7 g / mol.
[0013] Wherein, the amino alcohol used in the alcoholysis reaction of step 1) is at least one of the polymers or copolymers of amino alcohols selected from polyethylene glycol diamine, bis(3-aminopropyl) polyethylene glycol (CAS no.34901-14-9), poly(ethylene glycol) methyl ether amine (CAS no.80506-64-5), and O-(2-aminoethyl) polyethylene glycol (CAS no.32130-27-1), preferably bis(3-aminopropyl) polyethylene glycol, with a number average molecular weight of 1500 g / mol.
[0014] The weight ratio of the amino alcohol to the polylactic acid waste is 1:820 to 1:450. Since the amino alcohol in the present invention can catalyze alcoholysis of polylactic acid cracking reaction under the synergistic effect of the acidic catalyst, the amount of catalyst can complete the cracking reaction, but when the amount is too small, the cracking reaction rate is significantly reduced. For cost considerations, it is preferably 1:800.
[0015] Preferably, the alcoholysis reaction temperature is 180-220° C., and the reaction time is 1.5 hours.
[0016] Wherein, in step 1, the molecular weight of the polylactic acid oligomer is 1500-4000, preferably 1500-2500.
[0017] Wherein, the acidic catalyst in step 1 is at least one of stannous octoate, stannous chloride, stannous oxide, stannous n-butoxide, bismuth octoate, bismuth chloride, zinc octoate, zinc chloride, zinc oxide, ferrous chloride, calcium octoate, titanium octoate, chromium octoate, and barium octoate, preferably stannous oxide.
[0018] Wherein, the weight ratio of the acid catalyst to the polylactic acid waste is 1:10000 to 1:1000, preferably 1:5000.
[0019] The cracking reaction conditions in step 2 are 180-230° C., vacuum degree -0.1 to -0.095 MPa, preferably 200-230° C., vacuum degree -0.1 to -0.098 MPa. The reaction time is 2 to 5 hours, preferably 3 hours.
[0020] Wherein, the lactide content in the crude lactide in step 2) is above 80%.
[0021] Wherein, the melting sweating device in step 3) includes a double falling film melting crystallizer, a heating circulation pump, etc.
[0022] Wherein, the chemical purity of the purified lactide in step 3) is 99.8%, and the optical purity is above 99.5%.
[0023] Compared with the prior art, the technical advantages of the present invention are:
[0024] 1. The present invention uses amino alcohol to catalyze the chain scission and cracking of polylactic acid, thereby reducing the chain scission reaction temperature, reducing the generation of ester by-products, and improving the recovery rate of lactide.
[0025] 2. The synergistic catalysis of amino alcohol and acidic catalyst greatly reduces the amount of catalyst used. Since amino alcohol can form a complex with the metal ions in the acidic catalyst, the dispersibility of the acidic catalyst in the reaction system is improved, and the catalytic efficiency is greatly improved. The amount of amino alcohol added in step 1 is much lower than that of small molecule alcohol compounds such as methanol, ethanol, ethylene glycol, propylene glycol, butanediol, pentanediol, and hexanediol in existing patents. And both amino alcohol and acidic catalyst can be used repeatedly.
[0026] 3. Due to the use of amino alcohols, no by-products such as small molecule alcohols and esters are generated in the cleavage reaction. There is no need to use a large amount of solvent to remove small molecules during purification. High-purity refined lactide can be obtained through simple water washing and melt sweating purification.
[0027] 4. The present invention provides a new method for recycling polylactic acid. The method is simple, fast and has high production efficiency. It not only solves the problem of handling various types of polylactic acid waste, but also reduces the production cost of lactide, which is in line with the sustainable development policy. DETAILED DESCRIPTION
[0028] Embodiment 1:
[0029] Add 5kg of polylactic acid waste particles (levorotatory polylactic acid homopolymer, number average molecular weight 50000g / mol), 6.09g of poly(ethylene glycol) methyl ether amine (number average molecular weight 1000g / mol), and 1g of stannous oxide into the reactor, heat to 220℃ and stir for 2 hours to carry out alcoholysis reaction to prepare lactic acid oligomers. Sampling test shows that the molecular weight of lactic acid oligomers is 2100-2400. Thereafter, the reactor temperature is raised to 220℃, and the vacuum degree in the reactor is reduced to -0.098MPa, and the material is discharged. After 2.5 hours of discharge, the reaction is complete, and 4.4kg of lactide crude material is recovered. Among them, the lactide content is 85.7%, the dimer lactic acid content is 11.4%, the meso-lactide content is 1.2%, the trimer lactic acid content is 0.9%, and the lactic acid content is 0.8%. Wash the lactide crude material with water for 10 minutes, filter it and dry it to make the water content less than 0.5%. The dried lactide crude material is filled into a double falling film melt crystallizer, and the heating circulation pump is operated to heat the heat medium to 100°C to completely melt the lactide. The heat medium of the heating circulation pump is reduced to 80°C at a rate of 5°C per hour and maintained for 30 minutes to crystallize the lactide and discharge the uncrystallized residual liquid. The heat medium is heated to 95°C at a rate of 5°C per hour and maintained for 30 minutes for sweating treatment, and the sweating liquid is discharged. Thereafter, the temperature of the circulation pump is raised to 100°C to melt and discharge all the remaining lactide crystals. 3.61 kg of refined L-lactide is recovered, with a chemical purity of 99.9% and an optical purity of 99.8%.
[0030] Embodiment 2:
[0031] Add 5kg of polylactic acid waste particles (levorotatory polylactic acid homopolymer, number average molecular weight 50000g / mol), 6.09g of bis(3-aminopropyl) polyethylene glycol (number average molecular weight 1500g / mol), and 1g of stannous oxide into the reactor, heat to 200℃ and stir for 1.5 hours to carry out alcoholysis reaction to prepare lactic acid oligomers. Sampling test shows that the molecular weight of lactic acid oligomers is 1900-2300. Thereafter, the reactor temperature is raised to 210℃, and the vacuum degree in the reactor is reduced to -0.098MPa, and the material is discharged. After 2.5 hours of discharge, the reaction is complete, and 4.4kg of lactide crude material is recovered. Among them, the lactide content is 89.2%, the dimer lactic acid content is 8.9%, the meso-lactide content is 1.1%, the trimer lactic acid content is 0.1%, and the lactic acid content is 0.7%. Wash the lactide crude material with water for 10 minutes, filter it and dry it to make the water content less than 0.5%. The dried lactide crude material is filled into a double falling film melt crystallizer, and the heating circulation pump is operated to heat the heat medium to 100°C to completely melt the lactide. The heat medium of the heating circulation pump is reduced to 80°C at a rate of 5°C per hour and maintained for 30 minutes to crystallize the lactide and discharge the uncrystallized residual liquid. The heat medium is heated to 95°C at a rate of 5°C per hour and maintained for 30 minutes for sweating treatment, and the sweating liquid is discharged. Thereafter, the temperature of the circulation pump is raised to 100°C to melt and discharge all the remaining lactide crystals. 3.75 kg of refined L-lactide is recovered, with a chemical purity of 99.9% and an optical purity of 99.8%.
[0032] Embodiment 3:
[0033] Add 5kg of polylactic acid waste particles (levorotatory polylactic acid homopolymer, number average molecular weight 50000g / mol), 6.09g of bis(3-aminopropyl) polyethylene glycol (number average molecular weight 1500g / mol), and 1g of zinc oxide into the reactor, heat to 200℃ and stir for 2.5 hours to carry out alcoholysis reaction to prepare lactic acid oligomers. Sampling test shows that the molecular weight of lactic acid oligomers is 2000-2300. Thereafter, the reactor temperature is raised to 210℃, and the vacuum degree in the reactor is reduced to -0.098MPa, and the material is discharged. After 4 hours of discharge, the reaction is complete, and 4.3kg of lactide crude material is recovered. Among them, the lactide content is 80.5%, the dimer lactic acid content is 15.4%, the meso-lactide content is 1.3%, the trimer lactic acid content is 1.5%, and the lactic acid content is 1.3%. Wash the lactide crude material with water for 10 minutes, filter it and dry it to make the water content less than 0.5%. The dried lactide crude material is filled into a double falling film melt crystallizer, and the heating circulation pump is operated to heat the heat medium to 100°C to completely melt the lactide. The heat medium of the heating circulation pump is reduced to 80°C at a rate of 5°C per hour and maintained for 30 minutes to crystallize the lactide and discharge the uncrystallized residual liquid. The heat medium is heated to 95°C at a rate of 5°C per hour and maintained for 30 minutes for sweating treatment, and the sweating liquid is discharged. Thereafter, the temperature of the circulation pump is raised to 100°C to melt and discharge all the remaining lactide crystals. 3.37 kg of refined L-lactide is recovered, with a chemical purity of 99.8% and an optical purity of 99.8%.
[0034] Embodiment 4:
[0035] Add 5kg of polylactic acid waste particles (levorotatory polylactic acid homopolymer, number average molecular weight 300000g / mol), 6.09g of bis(3-aminopropyl) polyethylene glycol (number average molecular weight 1500g / mol), and 1g of stannous oxide into the reactor, heat to 220°C and stir for 2.5 hours to carry out alcoholysis reaction to prepare lactic acid oligomers. Sampling test shows that the molecular weight of lactic acid oligomers is 1900-2300. Thereafter, the reactor temperature is raised to 210°C, and the vacuum degree in the reactor is reduced to -0.098MPa, and the material is discharged. After 2.5 hours of discharge, the reaction is complete, and 4.4kg of lactide crude material is recovered. Among them, the lactide content is 88.5%, the dimer lactic acid content is 9.0%, the meso-lactide content is 1.4%, the trimer lactic acid content is 0.5%, and the lactic acid content is 0.6%. Wash the lactide crude material with water for 10 minutes, filter it and dry it to make the water content less than 0.5%. The dried lactide crude material is filled into a double falling film melt crystallizer, and the heating circulation pump is operated to heat the heat medium to 100°C to completely melt the lactide. The heat medium of the heating circulation pump is reduced to 80°C at a rate of 5°C per hour and maintained for 30 minutes to crystallize the lactide and discharge the uncrystallized residual liquid. The heat medium is heated to 95°C at a rate of 5°C per hour and maintained for 30 minutes for sweating treatment, and the sweating liquid is discharged. Thereafter, the temperature of the circulation pump is raised to 100°C to melt and discharge all the remaining lactide crystals. 3.71 kg of refined L-lactide is recovered, with a chemical purity of 99.9% and an optical purity of 99.8%.
[0036] Embodiment 5:
[0037] Add 5kg of polylactic acid waste particles (copolymer of left-handed polylactic acid and polyvinyl alcohol, number average molecular weight 150000g / mol, polylactic acid content 60%), 3.65g of bis(3-aminopropyl) polyethylene glycol (number average molecular weight 1500g / mol), and 0.6g of stannous oxide into the reactor, heat to 200°C and stir for 1.5 hours to carry out alcoholysis reaction to prepare lactic acid oligomers. Sampling test shows that the molecular weight of lactic acid oligomers is 3500-3700. Thereafter, the reactor temperature is raised to 210°C, and the vacuum degree in the reactor is reduced to -0.098MPa, and the material is discharged. After 1.5 hours of discharge, the reaction is complete, and 2.6kg of lactide crude material is recovered. Among them, the lactide content is 85.0%, the dimer lactic acid content is 11.1%, the meso-lactide content is 2.2%, the trimer lactic acid content is 0.9%, and the lactic acid content is 0.8%. Wash the lactide crude material with water for 10 minutes, filter and dry it to make the water content less than 0.5%. Fill the dried lactide crude material into a double falling film melt crystallizer, operate the heating circulation pump to heat the heat medium to 100°C, and melt the lactide completely. Reduce the heat medium of the heating circulation pump to 80°C at a rate of 5°C per hour and keep it for 30 minutes to crystallize the lactide and discharge the uncrystallized residual liquid. Raise the heat medium to 95°C at a rate of 5°C per hour and keep it for 30 minutes to sweat, discharge the sweating liquid, and then raise the temperature of the circulation pump to 100°C to melt and discharge all the remaining lactide crystals. Recover and refine 2.11kg of L-lactide with a chemical purity of 99.9% and an optical purity of 99.8%.
[0038] Embodiment 6:
[0039] Add 5kg of polylactic acid waste particles (a blend of left-handed polylactic acid and polyethylene, with a polylactic acid number average molecular weight of 100,000g / mol and a content of 20%), 1.21g of bis(3-aminopropyl) polyethylene glycol (number average molecular weight of 1500g / mol), and 0.2g of stannous oxide into a reactor, heat to 200°C, stir for 1 hour to carry out alcoholysis reaction to prepare lactic acid oligomers. Thereafter, the reactor temperature is raised to 210°C, and the vacuum degree in the reactor is reduced to -0.098MPa, and the material is discharged. After 1 hour of discharge, the reaction is complete, and 0.88kg of lactide crude material is recovered. Among them, the lactide content is 86.7%, the dimer lactic acid content is 9.6%, the meso-lactide content is 1.4%, the trimer lactic acid content is 1.4%, and the lactic acid content is 0.9%. The lactide crude material is washed with water for 10 minutes, filtered and dried to make the water content less than 0.5%. The dried lactide crude material is filled into a double falling film melt crystallizer, and the heating circulation pump is operated to heat the heat medium to 100°C to completely melt the lactide. The heat medium of the heating circulation pump is reduced to 80°C at a rate of 5°C per hour and maintained for 30 minutes to crystallize the lactide and discharge the uncrystallized residual liquid. The heat medium is heated to 95°C at a rate of 5°C per hour and maintained for 30 minutes for sweating treatment, and the sweating liquid is discharged. Thereafter, the temperature of the circulation pump is raised to 100°C to melt and discharge all the remaining lactide crystals. 0.69 kg of refined L-lactide is recovered, with a chemical purity of 99.9% and an optical purity of 99.8%.
[0040] Embodiment 7:
[0041] Other conditions were the same as in Example 2, except that the amount of bis(3-aminopropyl)polyethylene glycol was adjusted. The experimental results are shown in Table 1.
[0042] Table 1 Effect of amino alcohol dosage on lactide synthesis
[0043] Amino alcohol dosage (g) Crude lactide yield Refined lactide yield Chemical purity Optical purity 6.09 (Example 2) 99.2% 84.5% 99.9% 99.8% 3.33 78.9% 46.3% 97.6% 99.1% 4.80 82.9% 51.0% 98.1% 99.6% 11.1 99.5% 84.4% 99.9% 99.8% 25.0 99.4% 84.3% 99.9% 99.8%
[0044] From the data in the analysis table, it can be seen that a good catalytic effect can be obtained when the weight ratio of amino alcohol to polylactic acid is above 1:820, while when the weight ratio of amino alcohol to polylactic acid is less than 1:820, the reaction cannot be completed in a short time. For cost considerations, the minimum amount of 1:820 is selected as the most preferred.
[0045] Comparative Example 1:
[0046] Add 5kg of polylactic acid waste particles (levorotatory polylactic acid homopolymer, number average molecular weight 50000g / mol) and 200g of pentanediol into the reactor, heat to 200℃ and stir for 3 hours to carry out alcoholysis reaction to prepare lactic acid oligomers. Sampling test shows that the molecular weight of lactic acid oligomers is 1000-1400. Then add 15g of stannous chloride, raise the kettle temperature to 185℃, reduce the vacuum degree in the kettle to -0.098MPa, and start discharging. After 4 hours of discharging, the reaction is complete, and 3.7kg of lactide crude material is recovered. Among them, the lactide content is 71.3%, the lactic acid pentanediol content is 6.5%, the dimer lactic acid content is 16.7%, the meso-lactide content is 2.4%, the trimer lactic acid content is 1.9%, the lactic acid content is 1.0%, and the pentanediol content is 0.2%. The lactide crude material is dissolved in ethyl acetate and cooled for recrystallization, and lactide is obtained after suction filtration. Repeat the above steps 5 times and then vacuum dry to obtain 1.55 kg of refined L-lactide with a chemical purity of 99.5% and an optical purity of 99.8%.
[0047] Add 5kg of polylactic acid waste particles (levorotatory polylactic acid homopolymer, number average molecular weight 50000g / mol), 6.09g of polyethylene glycol (number average molecular weight 1000g / mol), and 1g of stannous oxide into the reactor, heat to 220℃ and stir for 2 hours to carry out alcoholysis reaction to prepare lactic acid oligomers. Sampling test shows that the molecular weight of lactic acid oligomers is 2100-2400. Thereafter, the reactor temperature is raised to 220℃, and the vacuum degree in the reactor is reduced to -0.098MPa, and the material is discharged. After 2.5 hours of discharge, the reaction is complete, and 4.4kg of lactide crude material is recovered. Among them, the lactide content is 85.7%, the dimer lactic acid content is 11.4%, the meso lactide content is 1.2%, the trimer lactic acid content is 0.9%, and the lactic acid content is 0.8%. Wash the lactide crude material with water for 10 minutes, filter it and dry it to make the water content less than 0.5%. Fill the dried lactide crude material into a double falling film melt crystallizer, and run the heating circulation pump to heat the heat medium to 100°C to completely melt the lactide. Reduce the heat medium of the heating circulation pump to 80°C at a rate of 5°C per hour and keep it for 30 minutes to allow the lactide to crystallize and discharge the uncrystallized residual liquid. Raise the heat medium to 95°C at a rate of 5°C per hour and keep it for 30 minutes to sweat, discharge the sweating liquid, and then raise the temperature of the circulation pump to 100°C to melt and discharge all the remaining lactide crystals. Recover 3.61 kg of refined L-lactide with a chemical purity of 99.9% and an optical purity of 99.8%. Comparative Example 3:
[0048] Add 5kg of polylactic acid waste particles (levorotatory polylactic acid homopolymer, number average molecular weight 50000g / mol), 6.09g of poly[acryloyl-bis(aminopropyl)polyethylene glycol] (number average molecular weight 1000g / mol), and 1g of stannous oxide into the reactor, heat to 220°C and stir for 2 hours to carry out alcoholysis reaction to prepare lactic acid oligomers. Sampling test shows that the molecular weight of lactic acid oligomers is 2100-2400. Thereafter, the reactor temperature is raised to 220°C, and the vacuum degree in the reactor is reduced to -0.098MPa, and the material is discharged. After 2.5 hours of discharge, the reaction is complete, and 4.4kg of lactide crude material is recovered. Among them, the lactide content is 85.7%, the dimer lactic acid content is 11.4%, the meso lactide content is 1.2%, the trimer lactic acid content is 0.9%, and the lactic acid content is 0.8%. Wash the lactide crude material with water for 10 minutes, filter it and dry it to make the water content less than 0.5%. The dried lactide crude material is filled into a double falling film melt crystallizer, and the heating circulation pump is operated to heat the heat medium to 100°C to completely melt the lactide. The heat medium of the heating circulation pump is reduced to 80°C at a rate of 5°C per hour and maintained for 30 minutes to crystallize the lactide and discharge the uncrystallized residual liquid. The heat medium is heated to 95°C at a rate of 5°C per hour and maintained for 30 minutes for sweating treatment, and the sweating liquid is discharged. Thereafter, the temperature of the circulation pump is raised to 100°C to melt and discharge all the remaining lactide crystals. 3.61 kg of refined L-lactide is recovered, with a chemical purity of 99.9% and an optical purity of 99.8%.
[0049] The lactide yields and qualities of Examples 1 to 6 and Comparative Examples 1 to 3 were compared, and the results are shown in Table 2:
[0050] Table 2 Yield and purity of L-lactide under different conditions
[0051]
[0052]
[0053] As shown in the above table, the quality of the final refined L-lactide obtained in Examples 1 to 6 is similar, and the difference is mainly reflected in the yield of crude product and finished product. In Examples 1 to 3, the types of amino alcohols and acidic catalysts used are adjusted for comparison. The crude lactide yield is above 95%, and the refined lactide yield is above 75%, which proves the reliability of the catalytic system proposed by the present invention. Compared with Examples 1 to 3, the comparative example uses pentanediol as the hydroxyl source used in alcoholysis, and alcoholysis and cracking are distributed. Since no acidic catalyst is added in the alcoholysis reaction, the amount of pentanediol used is high (4% weight fraction). And pentanediol is a small molecule, and its boiling point is close to the reaction temperature, so that a large amount of pentanediol vaporizes during the reaction and cannot be completely mixed with polylactic acid, and the reaction efficiency is low. During post-treatment, due to the use of small molecule diols, the crude lactide contains a large amount of lactic acid esters and residual pentanediol. The complex composition of the crude product makes it impossible to directly perform melt sweating refining on the product. Therefore, according to CN115403554A, the solvent dissolution and low temperature crystallization method are used for refining, resulting in a low final yield, and a large amount of organic solvents are used, resulting in a large amount of waste liquid, which increases the cost. In Comparative Example 2, polyethylene glycol is used as a catalyst for alcoholysis reaction. Since it cannot form ligands with metal ions, the catalytic efficiency is reduced compared with Examples 1 to 3. Under the conditions of alcoholysis for 2 hours used in the present invention, polylactic acid cannot be completely converted into lactic acid oligomers, resulting in a decrease in yield. In Comparative Example 3, poly [acryloyl-bis (aminopropyl) polyethylene glycol] (PEGA resin) is used as an amino alcohol catalyst for testing. The large number of side chains in the PEGA resin causes the hydroxyl group to be unable to rapidly undergo ester exchange reaction in the molten polylactic acid, and the alcoholysis effect is reduced. In addition, Examples 4 to 6 discuss the experimental results when using different types of raw materials, indicating that the process is widely applicable to waste materials of various qualities in practical application.
[0054] The present invention is not limited to the above-mentioned embodiments. On the basis of the technical solution disclosed in the present invention, technicians in this field can make some substitutions and deformations to some technical features therein according to the disclosed technical content without creative labor, and these substitutions and deformations are all within the protection scope of the present invention.
Claims
1. A method for synthesizing lactide by cracking polylactic acid waste, Features The steps include: 1) At 180-230°C, under the action of an acidic catalyst and amino alcohol, polylactic acid waste undergoes an ester exchange reaction under melting and stirring, and the polylactic acid molecular chain breaks to generate lactic acid oligomers, and the reaction time is 1-2 hours; 2) The number average molecular weight of the lactic acid oligomer obtained by chain scission in step 1) is 1500-2500 g / mol; the lactic acid oligomer undergoes a dehydration cyclization reaction under the conditions of 180-230° C. and -0.1-0.095 MPa vacuum to generate crude lactide; 3) The crude lactide produced is purified by melt sweating to obtain refined lactide.
2. A method for synthesizing lactide by cracking polylactic acid waste according to claim 1, It is characterized in that The polylactic acid waste in step 1) is a homopolymer, copolymer or blend of left-handed polylactic acid, right-handed polylactic acid, racemic polylactic acid or optically inactive polylactic acid; the polylactic acid content in the polylactic acid waste is 10% to 100%, and the number average molecular weight is 10 3 ~10 7 g / mol.
3. A method for synthesizing lactide by cracking polylactic acid waste according to claim 1, It is characterized in that The acid catalyst is an inorganic acid.
4. A method for synthesizing lactide by cracking polylactic acid waste according to any one of claims 1 to 3, It is characterized in that The amino alcohol is at least one of the polymers or copolymers of amino polyether polyols such as polyethylene glycol diamine, poly(ethylene glycol) methyl ether amine, bis(3-aminopropyl) polyethylene glycol, and O-(2-aminoethyl) polyethylene glycol.
5. A method for synthesizing lactide by cracking polylactic acid waste according to claim 4, It is characterized in that The weight ratio of the amino alcohol to the polylactic acid waste is 1:820 to 1:
450.
6. A method for synthesizing lactide by cracking polylactic acid waste according to any one of claims 1 to 3, It is characterized in that The acidic catalyst is at least one of stannous octoate, stannous chloride, stannous oxide, stannous n-butoxide, bismuth octoate, bismuth chloride, zinc octoate, zinc chloride, zinc oxide, ferrous chloride, calcium octoate, titanium octoate, chromium octoate, and barium octoate.
7. A method for synthesizing lactide by cracking polylactic acid waste according to claim 6, It is characterized in that The weight ratio of the acid catalyst to the polylactic acid waste is 1:10000 to 1:1000.
8. The method for synthesizing polyaniline fluorescent material based on click chemistry technology according to claim 7, It is characterized in that The molar ratio of the acidic catalyst to the amino alcohol is 1:10 to 1:1.
